2016
DOI: 10.1007/s10120-016-0679-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of long-term outcomes of endoscopic submucosal dissection and surgery for esophagogastric junction adenocarcinoma

Abstract: Background Endoscopic submucosal dissection (ESD) has become accepted as the standard treatment for early gastric cancer. However, comparative outcomes of ESD and surgery have not been evaluated for adenocarcinoma in the esophagogastric junction (EGJ). We investigated the longterm outcomes of ESD compared with those of surgery for adenocarcinoma in the EGJ. Methods Patients who underwent ESD or surgery for Siewert type II adenocarcinoma between 2005 and 2010 and who met the absolute and expanded criteria for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 28 publications
1
32
0
Order By: Relevance
“…The 5-year overall survival rates were similar in both groups. There was no gastric cancer related death in each group and the incidence of treatment-related adverse events was similar in both groups leading the authors to conclude that ESD may be an effective alternative to surgery with comparable long-term oncologic outcomes [27] . ESD has a good safety profile with low number of adverse events reported by many centers [28,29] .…”
Section: Role Of Endoscopic Treatment In Early Stage Gej Cancermentioning
confidence: 88%
“…The 5-year overall survival rates were similar in both groups. There was no gastric cancer related death in each group and the incidence of treatment-related adverse events was similar in both groups leading the authors to conclude that ESD may be an effective alternative to surgery with comparable long-term oncologic outcomes [27] . ESD has a good safety profile with low number of adverse events reported by many centers [28,29] .…”
Section: Role Of Endoscopic Treatment In Early Stage Gej Cancermentioning
confidence: 88%
“…Synchronous or metachronous lesions developed in 4 patients in ESD group. 26 (Figure 4 highlights post-ESD resection of T1 b lesions with central fibrosis and exposure of few muscularis propria fibers. )…”
Section: Survival Data For Patients With T1b Early Esophageal Cancer mentioning
confidence: 99%
“…Most cases were controlled with endoscopic hemostasis, clipping, or balloon dilation. In a comparative study with surgery, adverse events in the ESD group (10.0%) were similar to those in the surgery group (17.9%, p  = 0.308) [26]. In that study, 1 patient required emergency surgery due to uncontrolled bleeding in the ESD group, whereas 1 patient required surgery for ileus caused by internal herniation in the surgery group.…”
Section: Adverse Eventsmentioning
confidence: 99%
“…A larger study would be helpful in eliminating the long-term outcomes. One retrospective comparative study involving surgery demonstrated similar 5-year overall survival rates during the ESD and surgery during a long-term follow-up period (93.9 vs. 97.3%) [26]. No local recurrence and disease-specific death were observed.…”
Section: Long-term Outcomes Of Esdmentioning
confidence: 99%
See 1 more Smart Citation